Effect of Mg rates from different sources on cassava grown in Typic Paleustults - Apitsara Charoenphon; Suphicha Thanachit; Anusontpornperm, Somchai; Kheoruenromne, Irb (Agriculture and Natural Resources, 2021)
Three Typic Paleustults with low available Mg status, namely Yasothon (Yt), Warin (Wn), and Satuk (Suk) soil series, were selected for the study on the response of cassava to different rates of magnesium (Mg) from different sources. All field trials were similarly arranged in a randomized complete block design, having four replications with treatments comprising two sources of Mg fertilizer, dolomite and magnesium chloride (MgCl2) being applied at four rates, 0, 50, 100 and 200 kg Mg/ha. Results revealed that Mg content in selected soils before planting was insufficient for cassava due to the plot with no Mg addition in all soils statistically giving the lowest plant yield components. Cassava responded rather more positively to the rate of Mg applied than to the Mg sources. Cassava grown in chosen soils had a significant response Mg at varying rates of 50 to 200 kg Mg/ha. Dolomite was potentially a better source of Mg than MgCl2 in terms of increasing growth and yield of cassava, particularly in Wn soil series. Both Mg fertilizers added at the rates between 50–100 kg Mg/ha significantly promoted cassava to take up and accumulate more Mg and Ca in plant tissues. Relative tuber yield and aboveground biomass were better correlated with only major plant nutrients in leaf and branch than in other cassava plant parts.